1998
DOI: 10.1046/j.1432-1327.1998.2540610.x
|View full text |Cite
|
Sign up to set email alerts
|

NMR investigation of the multidrug transporter EmrE, an integral membrane protein

Abstract: EmrE is an Escherichia coli multidrug transport protein that confers resistance to a wide range of toxicants by active transport across the bacterial cell membrane. The highly hydrophobic polytopic integral membrane protein has been purified and studied in its full-length form by high-resolution NMR spectroscopy in a mixture of chloroform/methanol/water (6 :6:1, by vol.). Full activity is maintained after reconstitution of the protein into proteoliposomes from this solvent mixture. A series of heteronuclear ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
94
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 11 publications
7
94
0
Order By: Relevance
“…Three liquid state NMR studies on SMR proteins (EmrE and Smr) have been reported before (57)(58)(59). All studies used nonnative membrane mimicking conditions such as chloroform/ methanol for monomeric EmrE (59), lysopalmitoyl phosphatidylglycerol micelles for dimeric Smr (58), or biPC (1,2-di-Otetradecyl-and 1,2-di-O-hexyl-sn-glycero-3-phosphocholine spiked with ditetradecanoyl-/dihexanoylphosphatidylserine) bicelles for dimeric SMR (57).…”
Section: Interpretation Of Glu 14 Line Shape and Chemical Shiftsmentioning
confidence: 99%
“…Three liquid state NMR studies on SMR proteins (EmrE and Smr) have been reported before (57)(58)(59). All studies used nonnative membrane mimicking conditions such as chloroform/ methanol for monomeric EmrE (59), lysopalmitoyl phosphatidylglycerol micelles for dimeric Smr (58), or biPC (1,2-di-Otetradecyl-and 1,2-di-O-hexyl-sn-glycero-3-phosphocholine spiked with ditetradecanoyl-/dihexanoylphosphatidylserine) bicelles for dimeric SMR (57).…”
Section: Interpretation Of Glu 14 Line Shape and Chemical Shiftsmentioning
confidence: 99%
“…It is a small (110-residue) multidrug transporter that extrudes various positively charged drugs in exchange for protons, thus rendering bacteria resistant to these drugs (1)(2)(3). The protein has been characterized, purified, and reconstituted in a functional form (1,(4)(5)(6). High-affinity substrate binding has been established as a reliable and sensitive assay for activity of the detergent-solubilized transporter (4).…”
mentioning
confidence: 99%
“…MARS has been tested on 14 proteins ranging in size from the 71-residue Z domain of Staphylococcal protein A to 723-residue malate synthase G (Alattia et al, 2000;Gardner et al, 1998;Garrett et al, 1997;Ikura et al, 1991;Liu et al, 2000;Schwaiger et al, 1998;Tashiro et al, 1997;Tugarinov et al, 2002;Vathyam et al, 1999;Wang et al, 1995). Special focus was put on proteins that are challenging with respect to assignment either by their size or because chemical shifts are missing for a substantial portion of residues (Table 1).…”
Section: Testing Of Marsmentioning
confidence: 99%